EMBRACING DIVERSITY? A CONCEPTUAL EXPLORATION OF INFLUENCES ON STUDENT PARTICIPATION IN LGBT ACTIVITIES IN HIGHER EDUCATION” - Ahmad Effat bin Mokhtar; Wan Hashridz Rizal bin Wan Abu Bakar; Mohd Fikri bin Mokhtar; Abi Sofian bin Abdul Aziz (Journal of Islamic, Social, Economics and Development, 2023)
Recognizing the rising emphasis on diversity and inclusion, this study looks at the factors that influence student participation in LGBT activities in higher education. The study will use earlier research to uncover the characteristics that impact students' decisions to attend LGBT-related activities on campus. The term LGBT, which refers to sexual minority communities, exemplifies the evolving nature of inclusiveness. The study, which focuses on Malaysia, demonstrates the difficulties that the LGBT community suffers in a cultural and legal environment where same-sex relationships are considered taboo and illegal. The findings indicate the potential impact of cultural, religious, and legal factors on acceptance in Malaysian culture. The study provides insights into the various variables determining LGBT student engagement by investigating influencing factors such as natural personality, childhood sexuality role orientation, repercussions of sexual harassment, and peer influence. This study contributes to the greater conversation on diversity and inclusion in higher education by emphasizing the significance of having a sophisticated understanding of the difficulties that the LGBT community encounters.